Determining the net influence of biological processes on aqueous hydroxide-based ocean alkalinity enhancement: a mesocosm approach - Fucich, Derek; Lynch, Heather J.; Shaw, Cody; Eisaman, Matthew D.; Ringham, Mallory C. (Frontiers in Climate, 2025)
Ocean alkalinity enhancement (OAE) presents a promising means to leverage the ocean carbon sink to mitigate the effects of anthropogenic climate change. We report on a series of mesocosm experiments simulating electrodialysis-based OAE through the addition of aqueous sodium hydroxide to seawater in large tanks (~6,000 L) and small aquaria (~10 L) at Flax Pond Marine Laboratory, NY. In previous studies, the confounding effects of biological processes were controlled by imposing a sterilization treatment to seawater throughout each experiment. Here, we take the first steps in characterizing the influence of biological processes on OAE-based CO2 uptake through comparisons between sterilized and unsterilized mesocosms and aquaria. We combine our results with those of similar Flax Pond mesocosm experiments and develop a model to identify the most influential variables for determining the rate and magnitude of CO2 uptake. We found that the rate of CO2 uptake varies with changes in initial carbonate chemistry, the amount of alkalinity added, whether the mesocosm was sterilized, and the season in which the seawater was collected. Our model suggests that sterilized tanks did not differ in the amount of CO2 sequestered, but experienced a slower rate of equilibration relative to unsterilized tanks. These results indicate that laboratory mesocosm experiments could reasonably represent CO2 uptake in the field even with the complication of biological processes over the timeline of air-sea CO2 equilibration. This finding is valuable in supporting the measurement, reporting and verification of OAE, which must rely on a combination of laboratory data, near-field measurements, and modeling exercises.